Analysis of Urban Consumer Behavior for Fish in Tripura - Upadhyay, A.D.; Pandey, D.K. (Fishery Technology, 2025)
The consumer behavior towards fish consumption in Tripura is studied to analyze income and expenditure patterns of fish consumers' in urban area of Tripura and to examine consumers ' purchase and usage habits for fish. For the collection of data on households' income and expenditure, consumption of animal proteins and consumers' attitude towards fish consumption, 80 respondents were randomly selected from Agartala city, using cluster sampling technique. The information on income and expenditure of households, consumption pattern of fish and other non-vegetarian items and attitude towards fish consumption were collected through personal interview. The per capita fish consumption of fish in study area is higher than the consumption of chicken and mutton. The fish consumers prefer small sized, live/fresh and locally produced fish. The market prices of locally produced fishes are almost double than the fishes arrived from other states.